صيغ التعوذ وأبعادها البيانية في القرآن الكريم - حمادي، محمد (University of Eloued جامعة الوادي, 2024)
"هذه الدراسة الموسومة بــــــ: صيغ التعوذ وأبعادها البيانية في القرآن الكريم، وهي دراسة بلاغية لصيغ التعوذ وأبعادها البيانية الواردة في القرآن الكريم. وتتمحور حول إشكالية مفادها: أهم الصيغ التي استعملها القرآن الكريم للتعوذ ومدى أبعادها البيانية من خلال الأسلوب القرآني في استعمال التعوذ؟ وقد حاولت الإجابة عليها من خلال الإلمام بالموضوع من كل جوانبه وذلك بتقسيم البحث إلى مقدمة وثلاث مباحث وخاتمة. ففي المبحث التمهيدي عنيت من خلاله في إبراز مفهوم البيان القرآني وجهود العلماء في البحث فيه والتعرف على الصيغة الصرفية وأهميتها، والمبحث الثاني تناولنا تعريف التعوذ وصيغه الواردة في القرآن، وأما المبحث الثالث فهو المبحث التطبيقي تناولنا فيه دلالات صيغ التعوذ وأبعادها البيانية، فقمنا باستقراء مواضعها في كتاب الله العزيز. ختاما وفي نهاية الدراسة خلصنا إلى مجموعة من النتائج التي تعالج التساؤل المطروح حول إشكالية الدراسة وهي: أن جميع هذه الشرور لصيغ التعوذ الواردة في آيات القرآن ليس للمسلم في دفع وقوعها حيلة إلا الالتجاء إلى الله تعالى، وأن مصدر هذه الشرور الجن والإنس والنفس، وهذه مصادر الشر على المسلم. "This study is tagged with: the making of seeking refuge and its graphic dimensions in the holy Quran. Its is a rhetorical study of the nature of habituation and its graphic dimensions mentioned in the holy Quran, It revolves around a problem that states: the most important from used by holy Quran is seeking refuge and the extent of its graphic dimensions through the Quranic method of using habituation? I have tried to answer them through familiaity with the subject in all its aspects, by dividing the research into an introduction, three sections, and conclusion, in the introductory section, I highlighted the concept of the Quranic statement and the efforts of scholars to research it and identify the morphological formula and its importance the second section dealt with the definition of seeking refuge and its dimensions. Statements, so we extrapolated their location in the Mighty Book of God. Finally, at the end of the study, we concluded a set of results that address... The question raised about the problem of study is: All of these evils are habitual formulas mentioned in the verses of the Quran, and the Muslim has no means of preventing their occurrence except by resorting to God Almighty, and that the source of these evils is the jinn mankind and the soul, and these are source of evil for the Muslim"
مذكرة ماستر تخصص لغة ودراسات
Keywords: صيغ التعوذ; لقرآن الكريم; الأبعاد البيانية; Formulas of the talisman; the Holy Quran-graphic; graphic dimensions